Soret and dufour effect on the thin film flow over an unsteady stretching surface - Mustafa, M.; Shah, Q.; Gul, T.; Mamat, M.B.; Khan, W.; Tofany, N. (2016)
Thin film flow analysis with Soret and Dufour effects over an unsteady stretching surface have been studied in this research and this is the first attempt of any thin film fluid flow with Soret and Dufour. A uniform magnetic field has been applied transversely to the stretching surface. The similarity transformation has been used to transform the basic governing equations to a set of non-linear differential equations. The solution of these non-linear differential equations has been obtained by using Homotopy Analysis Method (HAM) and Numerical Shooting Method. The comparison of these two methods have been shown graphically and numerically with absolute error. The closed agreement between these two methods has also been obtained. The physical behavior of the modeled parameters like Prandtl number Pr, Dufour number Du, Schmidt number Sc, Soret number Sr and radiation constant Nr have been investigated through graphs and then discussed.